Simulations of the folding pathway of triose phosphate isomerase-type alpha/beta barrel proteins. - Godzik, A (1992)
Simulations of the folding pathways of two large alpha/beta proteins, the alpha subunit of tryptophan synthase and triose phosphate isomerase, are reported using the knight's walk lattice model of globular proteins and Monte Carlo dynamics. Starting from randomly generated unfolded states and with no assumptions regarding the nature of the folding intermediates, for the tryptophan synthase subunit these simulations predict, in agreement with experiment, the existence and location of a stable equilibrium intermediate comprised of six beta strands on the amino terminus of the molecule. For the case of triose phosphate isomerase, the simulations predict that both amino- and carboxyl-terminal intermediates should be observed. In a significant modification of previous lattice models, this model includes a full heavy atom side chain description and is capable of representing native conformations at the level of 2.5- to 3-A rms deviation for the C alpha positions, as compared to the crystal structure. With a well-balanced compromise between accuracy of the protein description and the computer requirements necessary to perform simulations spanning biologically significant amounts of time, the lattice model described here brings the possibility of studying important biological processes to present-day computers.